Parasitism by Ornithodoros faccinii (Ixodida: Argasidae) on Thoropa miliaris (Anura: Cycloramphidae) in Brazil. Issue 3 (3rd April 2017) - Sá-Hungaro, Iwine J. B.; Luz, Hermes R.; Lourenço, Elizabete C.; Silva, Hélio R.; Faccini, João L. H.; Famadas, Kátia M.
ABSTRACT: Ornithodoros faccinii Barros-Battesti, Landulfo & Luz 2015, a recently described species of soft tick, was collected from Thoropa miliaris (Spix, 1824), an amphibian of the family Cycloramphidae, in the municipality of Itaguaí, in the state of Rio de Janeiro. Primary aspects of the ecology of O. faccinii and its relationship with T. miliaris are still largely unknown. The aims of this study were to verify the distribution range, the presence of other stage and site preference for parasitism of O. faccinii on the anuran's body. To this end, 1026 specimens of T. miliaris from five important herpetological collections in Brazil were examined, 97 of which were parasitized by 433 larvae of O. faccinii . The geographical distribution of O. faccinii appears to be associated with that of T. miliaris, and several hypotheses are proposed regarding the behaviour of the larvae and the absence of parasitizing nymphs and adults. Thirteen municipalities in the state of Rio de Janeiro and other municipalities in the states of Minas Gerais, Espírito Santo and Bahia were added to the list of distribution of O. faccinii . No significant differences ( p  > 0.05) in parasitism were found among the categories of subadult, male and female. Twelve attachment sites were found for O. faccinii larvae, and the most frequently parasitized site on the body of T. miliaris was the inguinal region, followed by the lateral ventral and axillary regions. Parasitism by O. faccinii is highly aggregated in the regions under study in the state of Rio de Janeiro.